A (re)produção do espaço urbano no Bairro Altiplano, João Pessoa-PB: estratégias, iniciativas e interesses dos agentes que produzem a cidade - Fernandes, Maria Andreína Moreira (2013)
The present research approaches the spatial production in Altiplano neighborhood, located at the Eastside of João Pessoa city, which is currently the focus of an intense urban transformation. The publication of Local Ordinance n. 5844 in January 2007 allowed the densification of a determined area until than considered Additional Restricted Zone by the City Master Plan (1994). This resolution attracted upscale investments which started a rapid process of city verticalization up to be noticed and questioned under several features, since the environmental nature, going through the probably lost of cultural and landscaping values of the place, reaching reflections about applied urban legislature and the physical capability of the neighborhood to support the new demands. To analyze this region under the view of the production of the space was the trodden way to comprehend the city as a product of social working through the articulation between fields as the valorization, planning and occupation of urban space. So, the actual dissertation aims to evaluate the recently changes that characters the space production in the Altiplano neighborhood since the publication of Ordinance n. 5844/2007 and what relations they have with the strategies, initiatives and interests of production agents of the city about the whole urban dynamics field. To develop this work and obtain the intended objectives, it was necessary to establish three acting lines. The first refers to the bibliographic research intending to obtain a satisfactory theoreticalconceptual knowledge about two main themes necessary to the development of this dissertation. The second acting line is related to field research, composed by in loco visits, documental research and interviews applying. That was interviewed area acting incorporator´s representatives, architects e public employees related to urban planning. The third line of action corresponded to the organization and analysis of collected material, weaving reflections about the current situation, reasons and consequences of urban decisions applied in the area, and future occupancy tendencies of the sector by its relations with the whole city. The realized study reveals how the Altiplano have been produced by a complex game of influences and interests done by agents who interact between themselves framing the urban space construction and the real estate market dynamics of the city.